2023
DOI: 10.1158/2767-9764.crc-23-0243
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Assessment of Drug Synergy from In Vivo Combination Studies Using Mouse Tumor Models

Binchen Mao,
Sheng Guo

Abstract: Drug combination therapy is a promising strategy for treating cancer; however, its efficacy and synergy require rigorous evaluation in preclinical studies before going to clinical trials. Existing methods have limited power to detect synergy in animal studies. Here, we introduce a novel approach to assess in vivo drug synergy with high sensitivity and low false discovery rate. It can accurately estimate combination index and synergy score under the Bliss independence model and the highest single agent (HSA) mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…To rule out the impact of tumor size on anti-CTLA4 and nobiletin therapy, we selected tumors of similar size to those treated with IgG for anti-CTLA4 and/or nobiletin treatment, and the mice were given nobiletin (25 mg kg −1 ) daily and/or anti-CTLA4 (200 μg/mouse) once every 3 days. The tumor volume of each mouse was measured daily and combined with the invivoSyn method ( 46 ), the results showed that nobiletin and anti-CTLA4 combination therapy synergistically and most notably reduced tumor growth and tumor weight ( Fig. 7A and B ; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To rule out the impact of tumor size on anti-CTLA4 and nobiletin therapy, we selected tumors of similar size to those treated with IgG for anti-CTLA4 and/or nobiletin treatment, and the mice were given nobiletin (25 mg kg −1 ) daily and/or anti-CTLA4 (200 μg/mouse) once every 3 days. The tumor volume of each mouse was measured daily and combined with the invivoSyn method ( 46 ), the results showed that nobiletin and anti-CTLA4 combination therapy synergistically and most notably reduced tumor growth and tumor weight ( Fig. 7A and B ; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%